Analyzing Athlete-Family: A Bibliometric Study (2014–2024) - Seno Aji Wicaksono; Herman Subarjah; Wildan Akbar Firdaus; Dilal Hamdi (Universitas Negeri Semarang, 2025)
This study analyzes trends, patterns, and contributions of research on the relationship between athletes and their families using bibliometric analysis based on Scopus data from 2014–2024. Through VOSviewer software, it maps keywords, author collaboration networks, and the geographical distribution of publications, identifying the United States as the most productive and influential country in this field. Key themes include family support, mental health, and athlete motivation. The analysis reveals growing interest in this area, with fluctuating but overall increasing publications, peaking in 2023. A notable contribution is the article